Editorial (2020)
Universidad Santo Tomás, Secciona! Tunja, proudly presents the Principia Iuris journal No. 36. On this occasion, we share with the community a thematic issue on bio-rights, which has the participation of authors from all over the world, all of them international leaders in the development of this field. This is an impressive collection of works on the epistemology ofbiolaw and its applications, both in the legal and bioethical fields. We submit, then, to the scrutiny of the reader, articles from sorne of the most prominent experts in the field of biolaw and bioethics worldwide, which transforms this issue of our journal into an academic paradigm and milestone of international scope. On this occasion, as a courtesy, we have accepted that most authors quote their references in the footer. Our journal is indexed in EBSCO, Latindex, Publindex, Google Scholar, OpenAIRE and Open Archives. As always, the permanent and inexhaustible effort of the jurists and participants of this edition is highlighted by us and, with its greatness, by all the science of law.